2019
DOI: 10.1021/acssuschemeng.9b02798
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol (PEG) Addition to Polyethylenimine (PEI)-Impregnated Silica Increases Amine Accessibility during CO2 Sorption

Abstract: Amine-impregnated sorbents can be applied in CO2 sequestration, but they suffer from low amine utility due to slow diffusion of CO2, leading to reduced accessibility of buried amines. We examined silica-supported polyethylenimine (PEI) sorbents and blended them with polyethylene glycol (PEG) as an additive to study the role of PEG in modifying sorption performance. We report an increase in amine efficiency, a decrease in the heat of sorption and regeneration temperature, and a change CO2 amine speciation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…29,35−37 The maximum uncertainty in the calorimetry measurements is estimated to be 10 kJ mol −1 through previous experiments with a similar setup. 38 In stark contrast, C 2 H 4 adsorption on the core−shell nanoparticles was much less exothermic, measuring 125 kJ mol −1 for 2 ML Pt/TiWC and below instrumental detection limits (∼20 kJ mol −1 ) for 2 ML Pt/TiWN as would be expected from the differences in amounts of C 2 H 4 adsorption and reactivity trends. Although C 2 H 2 appeared to adsorb more strongly on the core−shell nanoparticles than on Pt comm (260−290 kJ mol −1 vs 200 kJ mol −1 ), the number of adsorbed C 2 H 2 molecules was an order of magnitude lower.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…29,35−37 The maximum uncertainty in the calorimetry measurements is estimated to be 10 kJ mol −1 through previous experiments with a similar setup. 38 In stark contrast, C 2 H 4 adsorption on the core−shell nanoparticles was much less exothermic, measuring 125 kJ mol −1 for 2 ML Pt/TiWC and below instrumental detection limits (∼20 kJ mol −1 ) for 2 ML Pt/TiWN as would be expected from the differences in amounts of C 2 H 4 adsorption and reactivity trends. Although C 2 H 2 appeared to adsorb more strongly on the core−shell nanoparticles than on Pt comm (260−290 kJ mol −1 vs 200 kJ mol −1 ), the number of adsorbed C 2 H 2 molecules was an order of magnitude lower.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Indeed, the heat of adsorption (Δ H ads ) measurements showed marked differences across samples. At 298 K, the Δ H ads for C 2 H 2 and C 2 H 4 on Pt comm was 200 kJ mol –1 and 190 kJ mol –1 , respectively, consistent with literature values. , The maximum uncertainty in the calorimetry measurements is estimated to be 10 kJ mol –1 through previous experiments with a similar setup . In stark contrast, C 2 H 4 adsorption on the core–shell nanoparticles was much less exothermic, measuring 125 kJ mol –1 for 2 ML Pt/TiWC and below instrumental detection limits (∼20 kJ mol –1 ) for 2 ML Pt/TiWN as would be expected from the differences in amounts of C 2 H 4 adsorption and reactivity trends.…”
Section: Resultsmentioning
confidence: 99%
“…This quality remains important and amines can also dynamically change the sorbent viscosity through intermolecular cross-linking between the PEI chains during sorption. 6,18 In the silica-supported PEI, the silica primarily provides both an increased surface area and mechanical support for the active sorbent. A recent study in thin-film sorption showed the performance of thin films comprising magnesium and a metal-organic framework (MOF), synthesized via vapor-assisted crystallization, with the film thicknesses ranging from 55 to 1300 nm.…”
Section: Introductionmentioning
confidence: 99%
“…17,21,22 In other literature reports, amines have been absorbed onto a physical framework. Utilizing solid supports such as mesoporous silica 16,23,24 and polymethylmethacrylate, 25,26 CO 2 sorption efficiency and kinetics were improved with an increased surface area for absorption and a simplified flow of gas. Solid absorbents have advantages over liquid-based systems: the CO 2 uptake can be higher, corrosion is minimized, properties such as ratios of amines to the solvent can be tuned, and viscosity changes with the CO 2 uptake are eliminated, which improves the gas flow.…”
Section: ■ Introductionmentioning
confidence: 99%